Numerical Solutions of Fractional Differential Equations by Using Laplace Transformation Method and Quadrature Rule - Samaneh Soradi-Zeid; Mehdi Mesrizadeh; Carlo Cattani (Fractal and Fractional, 2021)
This paper introduces an efficient numerical scheme for solving a significant class of fractional differential equations. The major contributions made in this paper apply a direct approach based on a combination of time discretization and the Laplace transform method to transcribe the fractional differential problem under study into a dynamic linear equations system. The resulting problem is then solved by employing the numerical method of the quadrature rule, which is also a well-developed numerical method. The present numerical scheme, which is based on the numerical inversion of Laplace transform and equal-width quadrature rule is robust and efficient. Some numerical experiments are carried out to evaluate the performance and effectiveness of the suggested framework.